PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL - Ichwanudin, Wawan; Istiqomah, Atika Rizki; Suryani, Emma (Jurnal Manajemen Sinergi, 2023)
ABSTRACTObjective: This study was conducted to evaluate the effect of profitability (ROA) on stock prices, considering capital structure (DER) as an intervening variable and company size as a control variable.Methodology: The sample in this study is a company incorporated in LQ45 on the Indonesia Stock Exchange which has complete data for the period 2018-2022. The data analysis method used is Path Analysis using the SPSS 20.0 program.Finding: The first, second, third, and fourth (H) hypotheses were accepted because the t statistic value was greater than t table, and the p value was smaller than alpha 0.05.Conclusion: The results indicate that ROA has a significant positive effect on stock prices. However, ROA has no significant effect on capital structure (DER), while DER has a significant negative effect on stock price. These results indicate that DER is unable to mediate the relationship between ROA and stock price. Firm size can serve as a control variable in the effect of profitability on stock price. This study shows important findings, that signaling theory can be confirmed where the profitability ratio is a positive signal for investors. However, it does not support the packing order theory because the capital structure is not influenced by profitability, so the capital structure does not mediate profitability on stock price.